Răspuns :
a-b = 42 si 2a = b-8⇒ a= 42 +b ⇒ 2 (42+b) = b-8 ⇒ 84 +2b = b-8 ⇒
⇒2b - b = -84 -8 ⇒ b = -92 deci se inlocuieste b cu -92 si obtinem :
a -(-92) =42 ⇒ a +92 = 42 ⇒ a = 42 - 92 ⇒ a = -50 verificam:
-50 -(-92) = 42: ⇒ -50+ 92= 42 ⇒ 42=42
Alta varianta:
a-b=42 si 2a = b-8
a =42+b deci 2(42+b)= b-8 ⇒ 84+2b= b-8 ⇒ 2b-b= -84-8 ⇒b= -92; inlocuim
in a -b=42:
a-(-92)=42 ⇒ a=42-92 ⇒a= -50
Rezultat: a= -50
b=-92
⇒2b - b = -84 -8 ⇒ b = -92 deci se inlocuieste b cu -92 si obtinem :
a -(-92) =42 ⇒ a +92 = 42 ⇒ a = 42 - 92 ⇒ a = -50 verificam:
-50 -(-92) = 42: ⇒ -50+ 92= 42 ⇒ 42=42
Alta varianta:
a-b=42 si 2a = b-8
a =42+b deci 2(42+b)= b-8 ⇒ 84+2b= b-8 ⇒ 2b-b= -84-8 ⇒b= -92; inlocuim
in a -b=42:
a-(-92)=42 ⇒ a=42-92 ⇒a= -50
Rezultat: a= -50
b=-92